(untitled) (Práxis Educativa, 2022)
The purpose of this article was to analyze how the black person is signified in didactic activities developed for Elementary School students, exposed on the social network Pinterest, to be applied in classrooms, on the National Day of Black Awareness. The discussions were based on social theories that deal with Law no. 10. 639, of January 9, 2003, and racial issues. The theoretical contribution of analysis was the Enunciative Semantics of the Event, a semantic theory developed by Professor Eduardo Guimarães, who considers the study of enunciation as the place where meaning is historically constructed in the subject’s relationship with language, in the event, and the text is seen as a complex unit of meaning that integrates utterances, which present in their functioning an internal consistency and a relative dependence, which give them meaning. The results of the analysis demonstrate that the activities published on the Pinterest network are marked by stereotypes that mean black people with the same meanings of past centuries, legitimizing discrimination and invisibility, fruits of racism still in force in the Brazilian society. Keywords: Meanings. Black. Teaching materials.